Development of a rubric to assess computational thinking skills among primary school students in Malaysia / Ling-Ling Ung, Jane Labadin and Saiful Nizam - Ung, Ling-Ling; Labadin, Jane; Nizam, Saiful (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
In the revised curriculum 2017, computational thinking skills have been integrated into the curriculum contents of all existing subjects in primary and secondary schools in Malaysia. The newly revised curriculum calls for an urgent need to prepare teachers to deliver computational thinking skills in the classroom and assess the teaching and learning outcomes of computational thinking skills. This paper reports the development of an assessment rubric, my CT Rubric, designed to evaluate the teaching and learning outcomes of the newly integrated computational thinking skills among primary school students in Malaysia. An action research approach guided the design and development of myCTRubric. myCTRubric was reviewed and validated by a panel of computational thinking subject matter experts. Analyses of results show that myCTRubric is reliable and has strong content validity. This pioneering work is expected to lend insights into the teaching and learning practices of computational thinking in Malaysian classrooms and served as a practical guideline for future research.